“What a Handsome Family We Are!”: Feral Children and Kin-Making in Abbie Farwell Brown’s The Book of Saints and Friendly Beasts (1900) - Julia Helena Wilde (European Journal of American Studies)
From the early modern period onwards, the phenomenon of feral children has led to ontological confusion and thus, has engendered both fascination and repulsion. A 1900 collection of short stories for children by American writer Abbie Farwell Brown titled The Book of Saints and Friendly Beasts seems, however, to depart from this way of thinking. The book includes two short stories about feral children who grow up to become saints (“Saint Keneth of the Gulls” and “The Wolf-Mother of Saint Ailbe”). The unusually close cross-species bonds presented by Brown in her stories can be considered as, what Donna Haraway, in Staying with the Trouble (2016), would call, “kin-making.” The aim of this article is to analyse the animality of the two feral boys as a formative element of their identity, stressing that it is the nonhuman Harawayan “oddkins” who shape their characters. Due to their unconventional upbringing, the boys become Catholic saints; crucially, the children choose not to renounce the familial bonds with their oddkins, which, in turn, presents a subtle shift in the portrayal of feral children.